2018
DOI: 10.5935/2595-0118.20180070
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block for perioperative analgesia in cardiac surgery. Case report

Abstract: BACKGROUND AND OBJECTIVES:The anesthetic management has evolved with the use of alternative techniques that promote greater safety, quick recovery and comfort in the perioperative period. The erector spinae plane block emerges as a promising alternative that can be employed as a simple analgesic technique for thoracic analgesia, acute post-surgical, post-traumatic and chronic neuropathic thoracic pain. CASE REPORT: Female patient, 72-year-old, undergoing aortic valve replacement surgery under general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…Bilateral ESPB led to requirement of no analgesia for the first 9 hours following aortic valve-replacement surgery. 49 In a patient undergoing emergency heart surgeries, bilateral ESPB was evaluated in a randomized controlled trial and found to decrease the total rescue analgesia and opioid requirements, as well as NRS scores, in the first 12 hours and also decrease time spent intubated. 50 A patient-matched controlled before-and-after study comparing the effects of bilateral ESPB (with catheter) with thoracic epidural analgesia on postoperative pain scores, opioid requirements, and time spent intubated found that extubation times were similar, NRS scores lower at some points but on average generally similar, and the first 48 hours' morphine consumption lower in the ESPB group (40 mg vs none).…”
Section: Thoracic and Cardiovascular Surgeriesmentioning
confidence: 99%
“…Bilateral ESPB led to requirement of no analgesia for the first 9 hours following aortic valve-replacement surgery. 49 In a patient undergoing emergency heart surgeries, bilateral ESPB was evaluated in a randomized controlled trial and found to decrease the total rescue analgesia and opioid requirements, as well as NRS scores, in the first 12 hours and also decrease time spent intubated. 50 A patient-matched controlled before-and-after study comparing the effects of bilateral ESPB (with catheter) with thoracic epidural analgesia on postoperative pain scores, opioid requirements, and time spent intubated found that extubation times were similar, NRS scores lower at some points but on average generally similar, and the first 48 hours' morphine consumption lower in the ESPB group (40 mg vs none).…”
Section: Thoracic and Cardiovascular Surgeriesmentioning
confidence: 99%
“…Even the optimal volume of local anesthetic to be administered to obtain the ESPB has not been established yet. [ 21 22 ] There are evidence suggesting a greater paravertebral spread after injection of 30 mL of local anesthetic. [ 23 ] And, based on this finding, a 40 mL volume of 0.375% Ropivacaine was chosen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions of this study are in line with Machado FC et al systematics review. 11 Our study's limitations were that we only evaluated at the efficacy of transdermal patches in postoperative patients who had just lower limb arthroscopic procedures, so additional research is needed to understand how well they work in other major surgeries. Furthermore, no individual medication dosage response curve studies were conducted.…”
Section: Discussionmentioning
confidence: 99%